Impact of Aerobic Exercise on Physical Health, Cardiorespiratory Parameters, and Health-Related Quality of Life Among Children With Diabetes Mellitus: A Narrative Review - Sharma, Abhishek; Sharma, Nidhi; Chahal, Aksh (Journal of diabetology, 2024)
Abstract Diabetes mellitus (DM) in children poses significant challenges to their physical health and overall well-being. While aerobic exercise (AE) has been extensively studied in managing DM, its role remains underexplored in the pediatric population. This narrative review aims to systematically evaluate the impact of AE on physical health, cardiorespiratory parameters, and health-related quality of life (HRQoL) in children with DM. A comprehensive literature review was conducted, focusing on studies examining AE interventions in children with DM. The review assessed the effects on physical health, cardiorespiratory fitness, and HRQoL, utilizing more commonly used HRQoL tools, such as the Pediatric Quality of Life Inventory (PedsQL). A total of eight studies with 589 participants were included in the review. The mean age of participants was 12.4 ± 2.8 years. Evidence indicates positive influences on cardiorespiratory parameters, including improved endothelial function, increased aerobic capacity, and better blood pressure control. HRQoL assessments reveal improved self-esteem, mood, and overall well-being, attributed to the physical and psychological benefits of regular exercise. AE holds significant potential as an adjunctive therapy to improve physical health, cardiorespiratory parameters, and HRQoL in children with DM. The comprehensive evaluation of social, psychological, and physical effects using HRQoL tools, such as PedsQL, and other factors, such as independent functioning, underscores the importance of integrating AE into diabetes management plans.